Al-Watsiniya fi al-katsulikiyah (al-bahts fi romziyu al-sholib) - Syamsul Hadi Untung, M.A, M.LS*; Amrina Rosyada* (Journal of Comparative Study of Religions (JCSR), 2021)
The cross is a symbol that is well known among the public as a symbol ofChristianity. Every sect in Christianity has a distinctive cross that distinguishes onefrom another. The Catholic and Protestant crosses are distinguished by the presenceof a corpus or statue of Jesus hanging on it. Catholics use a corpus on their crosses,whereas Protestants are just plain crosses without any statues. Researchers will tracedeeper into the history of the cross in pre-Christian times who rejected the presenceof the symbol of the cross because this symbol was only attached to people whohad committed grave sins. So that the researcher will use a historical methodologywith an approach to the manuscript literature related to the cross. The results foundby researchers that the meaning of the cross for Catholics today is taken from themeaning of the Pagan people because most Catholic teachings have been influenceand interfered with by the teachings of Paganism. The meaning of the cross as asymbol of the resurrection and atonement for sins by Jesus is like the god Bacchusin Pagan. In addition, the use of the cross in Catholic religious rituals is not muchdifferent from the worship of Pagan gods who also use the cross. In fact, the cross isa symbol of the god Mithra or the sun god who was later transformed into a symbolof God’s love through the death and resurrection of Jesus.